Impact of Exapion ulicis (Frster) (Coleoptera Apionidae) on gorse seed viability - Sixtus, C.R.; Hill, G.D.; Scott, R.R. (New Zealand Plant Protection, 2003)
As part of a study of gorse (Ulex europaeus L) biocontrol the effectiveness of the gorse seed weevil (Exapion ulicis (Frster)) in controlling the amount of viable seed was investigated Some seed attacked by gorse seed weevil still germinated with mean germination for lightly damaged seed being 18 and mean germination for heavily damaged seed being 4 Undamaged seed from damaged pods had high germination (mean 71) while undamaged seed from undamaged pods had a mean germination of 77 Many damaged seeds as well as undamaged seeds from damaged pods were infested by fungi (Fusarium spp and Cladosporium cladosporiodes) which affected the ability of the seeds to germinate There were no differences (P084) in the number of viable undamaged and damaged gorse seeds between the three sites sampled even though there were climatic differences and different soil types